The Influence of Social Media on HIV-Aids and LGBT Cases among the Young Generation in Jakarta - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Intan Silviana Mustikawati; Muniroh Muniroh; Puspita Chairun Nisa; Juniawan Mandala Putra; Arman Harahap (CV. Inara, 2025)
The study focused on the purpose of finding out the effect and the roles challenges faced by activists in the JPC Jakarta Foundation community in their efforts to prevent HIV and AIDS infections among LGBT people in Jakarta. This study applies a qualitative approach to observe the activities carried out by activists in three areas in the DKI Jakarta Province of Indonesia. The activities of the activists include field and online outreach, interactive group discussions, HIV counseling and testing, distribution of condoms and pelicans for LGBT youth, and social support for people living with HIV and AIDS (PLWHA). This study uses the theory of social action and symbolic interactionism to analyze the activities carried out by activists. This study found that the activities carried out by volunteer activists of the JPC Jakarta foundation in 2023. The study shows the results of the formation of rational-instrumental social action and a symbolic interaction in the context of HIV and AIDS prevention, with the LGBT community being a group affected by the increasing deviation of social media among the younger generation, especially Gen Z.